Estimation and sensitivity analysis of a COVID-19 model considering the use of face mask and vaccination - Zhongtian Bai; Zhihui Ma; Libaihe Jing; Yonghong Li; Shufan Wang; Bin-Guo Wang; Yan Wu; Xiaotao Han (Scientific Reports, 2023)
Abstract To model the COVID-19 infection and develop effective control measures, this paper proposes an SEIR-type epidemic model considering the impact of face-mask wearing and vaccination. Firstly, the effective reproduction number and the threshold conditions are obtained. Secondly, based on the data of South Korea from January 20, 2022 to March 21, 2022, the model parameters are estimated. Finally, a sensitivity analysis and the numerical study are conducted. The results show that the face-mask wearing is associated with $$83%$$ 83 % and $$90%$$ 90 % reductions in the numbers of cumulative cases and newly confirmed cases, respectively, after a period of 60 days, when the face mask wearing rate increases by $$15%$$ 15 % . Furthermore, the vaccination rate is associated with $$75%$$ 75 % and $$80%$$ 80 % reductions in the numbers of cumulative cases and the newly confirmed cases, respectively, after the same period of 60 days when the vaccination rate is increased by $$15%$$ 15 % . A combined measure involving face-mask wearing and vaccination may be more effective and reasonable in preventing and controlling this infection. It is also suggested that disease control departments should strongly recommended the wearing of face masks s as well as vaccination to prevent the unvaccinated people from becoming infected.